All-round enhancement induced by oxophilic single Ru and W atoms for alkaline hydrogen oxidation of tiny Pt nanoparticles - Wensheng Jiao; Zhanghao Ren; Zhibo Cui; Chao Ma; Ziang Shang; Guanzhen Chen; Ruihu Lu; Tao Gan; Ziyun Wang; Yu Xiong; Yunhu Han (Nature Communications)
Abstract Anion exchange membrane fuel cells (AEMFCs) are one of the ideal energy conversion devices. However, platinum (Pt), as the benchmark catalyst for the hydrogen oxidation reaction (HOR) of AEMFCs anodes, still faces issues of insufficient performance and susceptibility to CO poisoning. Here, we report the Joule heating-assisted synthesis of a small sized Ru1Pt single-atom alloy catalyst loaded on nitrogen-doped carbon modified with single W atoms (s-Ru1Pt@W1/NC), in which the near-range single Ru atoms on the Ru1Pt nanoparticles and the long-range single W atoms on the support simultaneously modulate the electronic structure of the active Pt-site, enhancing alkaline HOR performance of s-Ru1Pt@W1/NC. The mass activity of s-Ru1Pt@W1/NC is 7.54 A mgPt+Ru -1 and exhibits notable stability in 1000 ppm CO/H2-saturated electrolyte. Surprisingly, it can operate stably in H2-saturated electrolyte for 1000 h with only 24.60 % decay. Theoretical calculations demonstrate that the proximal single Ru atoms and the remote single W atoms synergistically optimize the electronic structure of the active Pt-site, improving the HOR activity and CO tolerance of the catalyst.